Emerging competencies for logistics professionals in the digital era: A literature review - Koh, Le Yi; Yuen, Kum Fai (Frontiers in Psychology, 2022)
The speed of technology integration among businesses has accelerated during the COVID-19 pandemic due to the work-from-home arrangements and safe distancing regulations, prompting businesses to automate operations and digitalize work environments. These impacts have disrupted work environments and operational processes, and a fresh set of competencies is required to stay competent in this new normal. Consequently, there is a need to develop a state-of-the-art competency framework for logistics professionals during these trying times. This study has adopted the Preferred Reporting Items for Systematic Reviews and Meta-Analyses to review, identify, and update the emerging competencies required by logistics professionals. The relevant academic documents were narrowed down to 81 and were used to identify the emerging competencies relevant to Industry 4.0 and COVID-19. The competencies were subsequently categorized into four key domains i.e., business, logistics, digital and personal competencies, with a total of 17 sub-domains. This state-of-the-art framework contributes to academic research by updating the existing competency frameworks. Future research can also build upon this holistic list of emerging competencies by utilizing it to reduce the competency gaps faced by those who are less technology savvy i.e., older logistics professionals. Additionally, future research can correlate the competency framework to organizational learning theories to improve the overall performance of logistics companies.